Telewizja tematyczna w obliczu nowych mediów - Kalisz, Aleksandra (Postscriptum Polonistyczne, 2020)
The article describes two television channels: a general one (TVN) and its thematic variation (TVN Style) in the context of transformations observed in the genological and discursive character of television itself. Analysis of the programme schedules of both TV channels reveals a tendency to create specific genres, it distinguishes certain types of speech that appear in both channels and presents the style of some magazines. Such presentation leads to certain conclusions on the essence of thematic television and the task it is to fulfil.